Organizational life cycle models: A design perspective - Luigi Mosca; Martina Gianecchini; Diego Campagnolo (Journal of Organization Design, 2021)
New competitive and environmental challenges have fostered renewed attention towards organizational design. This scenario calls for a significant return to organizational design studies that embrace a holistic approach, especially those focusing on the simultaneous interaction of multiple design elements. Organizational life cycle (OLC) models provide a fitting response to this call. In this paper, we review the organizational design characteristics of five seminal OLC models. We show that according to these OLC models, growth in size - which is described as unavoidable - generates business issues that firms are forced to solve by adopting only one possible organizational configuration, here following a deterministic organizational approach. We challenge this approach and propose conceiving of OLC as an evolutionary process, which calls for a variety of equifinal organizational solutions. We conclude by proposing future research avenues.
Keywords: 650; Organizational life cycle; Organizational design; Vertical differentiation; Horizontal differentiation; Centralization